Glibenclamide Improves Survival and Neurologic Outcome After Cardiac Arrest in Rats*. Issue 9 (September 2015) - Huang, Kaibin; Gu, Yong; Hu, Yafang; Ji, Zhong; Wang, Shengnan; Lin, Zhenzhou; Li, Xing; Xie, Zuoshan; Pan, Suyue
<x xml:space="preserve">Abstract</x> Objectives: Glibenclamide confers neuroprotection in animal models as well as in retrospective clinical studies. This study determines whether glibenclamide improves outcome after cardiac arrest in rats. Design: Prospective randomized laboratory study. Setting: University research laboratory. Subjects: Male Sprague-Dawley rats (n = 126). Interventions: Rats successfully resuscitated from 8-minute asphyxial cardiac arrest were randomized to glibenclamide or vehicle group. Rats in the glibenclamide group were intraperitoneally administered glibenclamide with a loading dose of 10 μg/kg at 10 minutes and a maintenance dose of 1.2 μg at 6, 12, 18, and 24 hours after return of spontaneous circulation, whereas rats in the vehicle group received equivalent volume of vehicle solution. Measurements and Main Results: Survival was recorded every day, and neurologic deficit scores were assessed at 24, 48, and 72 hours and 7 days after return of spontaneous circulation (n = 22 in each group). Results showed that glibenclamide treatment increased 7-day survival rate, reduced neurologic deficit scores, and prevented neuronal loss in the hippocampal cornu ammonis 1 region. To investigate the neuroprotective effects of glibenclamide in acute phase, we observed neuronal injury at 24 hours after return of spontaneous circulation and found that glibenclamide significantly decreased the rate of neuronal necrosis and apoptosis. In addition, glibenclamide reduced the messenger RNA expression of tumor necrosis factor-α and monocyte chemoattractant protein-1 in the cortex after return of spontaneous circulation. Furthermore, the sulfonylurea receptor 1 and transient receptor potential M4 heteromers, the putative therapeutic targets of glibenclamide, were up-regulated after cardiac arrest and cardiopulmonary resuscitation, indicating that they might be involved in neuroprotective effect of glibenclamide. Conclusions: Glibenclamide treatment substantially improved survival and neurologic outcome throughout a 7-day period after return of spontaneous circulation. The salutary effects of glibenclamide were associated with suppression of neuronal necrosis and apoptosis, as well as inflammation in the brain.